Primeira pessoa do plural em dossiê da revista Cult: traços de modalização - Bini, Renan Paulo (2018)
This research aims at investigating the use of the first person of plural in journalistic texts, so, it is taken into account the hypothesis that this subject of discourse can add epistemic modalization and different sense instances to the text, which are associated to ethos, pathos and logos categories of Rhetoric. Cutouts with occurrences on the first person of plural are analyzed in the text named as Feminist Conscience and Struggles: conquests and challenges in Brazil. This text shows the dossier Perceptions of Feminine and Feminist Actions, published in Cult/Edition Journal, 210/2016. The first query of this research is: could the first person of plural form delimit modifying effects in journalistic texts, as it happens in the cutouts selected for this analysis? Thus, in order to answer this demand, the overall goal of this research was verifying how the first person of plural works, as a modifying element and a rhetoric characteristic, in the text Conscience and feminist struggles: achievements and challenges in Brazil, concerning the Perceptions of Feminine and Feminist Actions dossier, in Cult Magazine. Thus, this study is explained by the state of art achievement has shown that there is little research on the PPP operation in journalistic texts and few researches that consider the PPP a rhetorical strategy. Regarding the use of this person's speech as a modalization strategy, no research was detected in the consulted academic databases. So, according to this subject, there is a perspective that discussion in journalistic texts is built up from the relationship among the text producer, textual subject-matter and the public-reader; and that the text producer handles with linguistic resources to act out on audience, in order to guide the meaning production when choosing content that will verbalize as well as how to do it, adhering to modalization. Thus, the theoretical basis of this research is constituted of research on Modalization and Rhetoric. Considering the evaluation of modification phenomena, there was some reflection on proposals such as those ones of Castilho and Castilho (1993), Campos (2001), Koch (2002), Miranda (2005) and Corbari (2013). Therefore, Mosca (2001), Aristotle (2017), Massmann (2017) and Perelman and Olbrechts-Tyteca (2017), among other researchers were studied to evaluate the rhetorical process. Sociolinguistic guidelines are also considered regarding the use of pronoun "we", as it can be observed in Lucchesi's proposal (2009), since it is a recurrent linguistic impress in corpus, considering engagement way of the text producer with the other persons of the discourse, although the author proposes categories when observing oral texts and this research aims at analyzing the written ones. The analyzes of the selected cutouts have shown that this person of discourse presents three dimensions of meaning in the text. It is highlighted that, although it concerns about a person of the discourse, the linguistic resource guides the senses in the text, if it is considered duly associated to the content of statements and image that is built of the text producer with the likely audience.